Interface conjugation enhances the interface adhesion performance of carbon fiber-reinforced phthalonitrile composites by π–π stacking. Issue 67 (14th November 2018) - Yin, Changping; Sheng, Liping; Yang, Yudong; Liang, Gengyuan; Xing, Suli; Zeng, Jingcheng; Xiao, Jiayu
Abstract : Cross-linking products and graphene can interact with each other through π–π stacking and promote the formation of interface conjugation. Abstract : There has been little research focus on the interface problems of phthalonitrile (PN) resin and carbon fiber. However, interface performance is related to the overall mechanical properties of composites and is very important. This study focused on the interfacial performance and adhesion mechanism of a carbon fiber Cf /PN composite. Micro-composites of Cf /PN and Cf /epoxy resins were prepared, and their interfacial shear strengths (IFSS) were tested by micro-droplet testing. The result showed that the IFSS of Cf /PN was higher than that of Cf /epoxy resin, indicating that the interfacial adhesion of the PN matrix composite must be more effective. To explain the obtained results, a number of tests, including SEM, SEM-EDS, FTIR, and TGA, were carried out. From the SEM analyses, cured PN polymer films were found on the surface of de-bonded carbon fibers. With the aid of SEM-EDS, the elements on the de-bonded carbon fiber surface of the Cf /PN composite were detected in situ . An interesting synchronous relationship was observed in the IFSS and SEM-EDS results. Through the FTIR spectra, the chemical structures of the PN polymers were identified. From the detailed analyses and discussion in this work, the effective interfacial bond function in the Cf /PN composite appears to be a complex result for all relative functions. The functional advantage of the PN composite may be the interface conjugation between the PN polymers and the graphene layer on the surface of the carbon fiber.